The effect of private pension funds’ bidding on fees and competition - Guillén Uyen, Jorge (2016)
This paper sheds light on the effect of bidding recent private pension funds on fees and competition. In order to accomplish the latter result, we used panel data of ten Latin American countries organized in quarters from 2005-2015. The reform of the private pension system in some countries in the region allows for the implementation of a mechanism of auctions on fees to capture new members. The objective of this mechanism was to drop fees and promote competition. We concluded that the effect on fees is successful since fees dropped while the effect on competition is ambiguous according to our panel data model and the measurement of efficiency. Results are relevant to regulate policies in the market of precautionary savings.